1997
DOI: 10.1128/jb.179.1.24-30.1997
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponses in Rhodobacter sphaeroides: role of photosynthetic electron transport

Abstract: Rhodobacter sphaeroides responds to a decrease in light intensity by a transient stop followed by adaptation. There is no measurable response to increases in light intensity. We confirmed that photosynthetic electron transport is essential for a photoresponse, as (i) inhibitors of photosynthetic electron transport inhibit photoresponses, (ii) electron transport to oxidases in the presence of oxygen reduces the photoresponse, and (iii) the magnitude of the response is dependent on the photopigment content of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 31 publications
6
42
1
Order By: Relevance
“…Previously it has been shown, in that chemotaxis to the dominant chemoattractants such as succinate and propionate requires transport and partial metabolism Ingham and Armitage, 1987;Jacobs et al, 1995). It is possible, therefore, that the second chemosensory pathway may sense the metabolic state of the cell through, for example, the electron-transport chain (Grishanin et al, 1997 ). Redoxsensing proteins such as FixL and ArcA (de Philip et al, 1990;Iuchi et al, 1990) are well characterized in bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Previously it has been shown, in that chemotaxis to the dominant chemoattractants such as succinate and propionate requires transport and partial metabolism Ingham and Armitage, 1987;Jacobs et al, 1995). It is possible, therefore, that the second chemosensory pathway may sense the metabolic state of the cell through, for example, the electron-transport chain (Grishanin et al, 1997 ). Redoxsensing proteins such as FixL and ArcA (de Philip et al, 1990;Iuchi et al, 1990) are well characterized in bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the chemotactic signal results from changes in the redox state of a component of the electron-transport chain, with NADH providing the link between sugar metabolism and electron transport, particularly as mannitol elicits such a strong response and requires a dehydrogenase as the first metabolic step. Redox sensors such as the PrrA/PrrB two-component system, which is involved in the oxygen control of photosynthesis gene expression, are well characterized in R. sphaeroides (Eraso & Kaplan, 1994, 1995 and recent work in this laboratory has shown that redox sensing is involved in tactic responses to light and oxygen (Grishanin et al, 1997). Current work is focused on the identification of the 'sensor' which may link metabolism and electron transport.…”
Section: Discussionmentioning
confidence: 99%
“…These results have led to the current dogma that the scotophobic response is mediated by the perception of a sudden decrease in the rate of photosynthesis rather than by light absorption through a specific photoreceptor. The mechanism of measuring a reduction in the efficiency of photosynthesis appears to involve monitoring alterations in the rate of photosynthesis-driven electron transport (10,14).The use of the bacterium Rhodospirillum centenum as a model organism for studying bacterial photoperception is particularly appealing since it is known to exhibit two distinctive photosensory processes (29,30). When grown in liquid medium, R. centenum cells, which are motile by means of a single polar flagellum, exhibit a typical scotophobic response.…”
mentioning
confidence: 99%
“…These results have led to the current dogma that the scotophobic response is mediated by the perception of a sudden decrease in the rate of photosynthesis rather than by light absorption through a specific photoreceptor. The mechanism of measuring a reduction in the efficiency of photosynthesis appears to involve monitoring alterations in the rate of photosynthesis-driven electron transport (10,14).…”
mentioning
confidence: 99%